Implementation of ERP at the Higher Education Institutions (HEIs): Challenges and benefits - Merouani Hamida; Boudjemil Ahmed (المجلة الدولية للأداء الاقتصادي, 2024)
The study aims to investigate the integration of Enterprise Resource Planning (ERP) systems in higher education institutions (HEIs) and emphasize their impact on improving administrative and educational processes, as well as the main challenges they may face. This study adopts a qualitative case study approach to analyze the implementation of ERP systems SAP and PROGRES across different institutions. The findings highlight the importance of strong administrative support, staff training, and robust infrastructure for successful ERP implementation. However, challenges such as resistance to change and resource constraints were also identified. Despite these challenges, ERP systems provide significant opportunities for HEIs to enhance the quality of administrative and educational processes and improve decision-making.